A Static Condensation Reduced Basis Element Approach for the Reynolds Lubrication Equation (Communications in Computational Physics, 2018)
In this paper, we propose a Static Condensation Reduced Basis Element(SCRBE) approach for the Reynolds Lubrication Equation (RLE). The SCRBE method isa computational tool that allows to efficiently analyze parameterized structures whichcan be decomposed into a large number of similar components. Here, we extend themethodology to allow for a more general domain decomposition, a typical examplebeing a checkerboard-pattern assembled from similar components. To this end, weextend the formulation and associated a posteriori error bound procedure. Our motivationcomes from the analysis of the pressure distribution in plain journal bearingsgoverned by the RLE. However, the SCRBE approach presented is not limited to bearingsand the RLE, but directly extends to other component-based systems. We shownumerical results for plain bearings to demonstrate the validity of the proposed approach.